Development and Implementation of Chemistry STEM-Based Module on Buffer Solution Material in Senior High School - Siregar, Litani; Silaban, Saronom (UNDIKMA, 2023)
One of the issues class XI SMA Negeri 1 Purba students encounter is that the teaching materials still used aren't very diverse; they mostly consist of textbooks, which makes it difficult for students to comprehend the material in the textbook. The goal of this study is to create a STEM-based chemistry module that will enhance student learning outcomes and activities. Research and development (R&D) using the ADDIE development model is the research methodology applied. This STEM-based chemistry module scored on average 89.47% for content feasibility, 90.17% for presentation feasibility, 95.31% for STEM assessment, 82.69% for language feasibility, and 95.16% for graphics, placing it in the category of being